2000
DOI: 10.1021/np990503m
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Stereochemistry of Nardostachysin, a New Terpenoid Ester Constituent of the Rhizomes of Nardostachys jatamansi

Abstract: The structure and stereochemistry of a new terpenoid ester, nardostachysin (1), isolated from the rhizomes of Nardostachys jatamansi, were established as the 7',8'-dihydroxy-4'-methylene hexahydrocyclopenta[c]pyran-1'-one-8'-methyl ester of 7, 9-guaiadien-14-oic acid, by spectral and chemical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 3 publications
0
21
0
Order By: Relevance
“…It has protective effect in parkinsonism, epilepsy, cerebral ischemia, liver damage. Various sesquiterpenes (such as Jatamansic acid and Jatamansone) have been reported to be present in the rhizomes of the plant [202]. …”
Section: Introductionmentioning
confidence: 99%
“…It has protective effect in parkinsonism, epilepsy, cerebral ischemia, liver damage. Various sesquiterpenes (such as Jatamansic acid and Jatamansone) have been reported to be present in the rhizomes of the plant [202]. …”
Section: Introductionmentioning
confidence: 99%
“…A 50% ethanol extract of Nardostachys jatamansi (whole plant) feeding has been found to increase HDL-cholesterol/total cholesterol ratio and also caused a significant reduction in the ratio of total cholesterol/phospholipids (Dixit et al, 1988). Recent studies showed that extracts of the rhizomes of Nardostachys jatamansi also contain hepatoprotective compounds (Ali et al, 2000) and studies have been conducted to elucidate the chemical structure of the active ingredients of this plant (Chatterjee et al, 2000). The present study was undertaken to examine the potential anticonvulsant activity of Nardostachys jatamansi, and the effect of combined treatment of Nardostachys jatamansi and phenytoin in particular, using the maximal electroshock seizure (MES) model.…”
Section: Introductionmentioning
confidence: 99%
“…jatamansi has been indicated in ayurvedic text to be a potent cardiotonic agent. A number of active components were also isolated from this plant 54) which includes lignans, sesquiterpenes and terpenoids. It has been reported that these compounds possess the cardioprotective effect through antioxidant defense mechanism.…”
Section: Discussionmentioning
confidence: 99%